Business Model Canvas Analysis of the Pexita MSME’s Community in Bekasi: A Case Study in Muslimadani - Oktavani, Nabila; Oktaviani, Nuriana; Hayati, Ayu Khusnul; Damayanti, Muthia Adisty; Jariyah, Widiyati; Maulina, Anita (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
Muslimadani, a micro, small, and medium enterprise (MSME), specializes in the production and marketing of men’s clothing, including koko shirts, sirwal, robes, and kurtas for children, adolescents, and adults. This study aims to identify and analyze the challenges, constraints, and potential solutions within Muslimadani’s business model canvas. A descriptive qualitative method was employed. The main issues faced by Muslimadani include rapidly shifting fashion trends and intense competition in both local and online markets such as TikTok, Shopee, Lazada, and Tokopedia. The Business Model Canvas framework is applied to examine key business components: customer segments, value propositions, channels, customer relationships, revenue streams, key resources, key activities, key partnerships, and cost structure. Muslimadani operates three physical outlets located in Tanah Abang Market (Central Jakarta), Umair Store (Malang), and Goro Assalam Wholesale Center (Solo), and actively markets its products through various online platforms. Through a combined analysis of the Business Model Canvas, STP (Segmentation, Targeting, and Positioning), and SWOT, this study suggests that Muslimadani has the potential to enhance sales and broaden its market share by strategically targeting the right customer segments and positioning its products effectively